2019
DOI: 10.1007/s10900-019-00783-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Secondhand Marijuana Smoke (SHMS) Exposure in Two New York City (NYC) Subsidized Housing Settings, 2018: NYC Housing Authority and Lower-Income Private Sector Buildings

Abstract: Introduction:The percentage of adults in the United States reporting current marijuana use has more than doubled, from 4% to 9% between 2002 and 2018, suggesting that exposure to secondhand marijuana smoke (SHMS) has probably increased. Few studies have characterized the extent to which residents experience SHMS, particularly those living in multi-unit housing. It remains unknown how recently implemented smoke-free housing policies (SFH) targeting cigarette smoke in public housing authorities (PHAs) will affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Our study is the first to highlight the role of local marijuana laws in undermining the SFH policy which was developed at the federal level. NYCHA residents reported that exposure to marijuana smoke was often greater than cigarette smoke [ 31 ]. With the loosening of enforcement in states where marijuana use remains illegal, and the spread of legalization across the U.S., it is likely that other PHAs are experiencing a rise in the prevalence of indoor exposure to marijuana smoke (which is currently not included or enforceable under the HUD’s SFH policy).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to highlight the role of local marijuana laws in undermining the SFH policy which was developed at the federal level. NYCHA residents reported that exposure to marijuana smoke was often greater than cigarette smoke [ 31 ]. With the loosening of enforcement in states where marijuana use remains illegal, and the spread of legalization across the U.S., it is likely that other PHAs are experiencing a rise in the prevalence of indoor exposure to marijuana smoke (which is currently not included or enforceable under the HUD’s SFH policy).…”
Section: Discussionmentioning
confidence: 99%
“…30 For marijuana, our results reveal incursion disparities among families living in financially supported housing compared with private housing (66.7% vs 25.8%), similar to previous studies. 19,20 Our study provides insight into the experience of smoke incursions during the early pandemic when children were spending most of their time indoors. Families in financially supported housing were more likely to report an increase in both tobacco and marijuana smoke incursions than those in private housing.…”
Section: Discussionmentioning
confidence: 95%
“…The health effects of SHMS exposure are not yet clearly understood; however, evidence suggests a link between psychoactive effects and impaired endothelial function 18. Similar to tobacco, marijuana smoke incursions can occur and have been more commonly reported in public housing than in private housing 19,20. A metabolite of marijuana, COOH-THC, has been detected in children living in NYC apartments 21.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, research into SHS transfer has expanded to include marijuana smoke. In self‐reported surveys, second‐hand marijuana smoke (SHMS) incursions in MURBs have been reported by 35.5% 77 and 67% 78 of respondents. While SHMS poses a similar IAQ and IEQ problem to SHS, much is still unknown regarding the relative magnitudes of inter‐zonal pollutant transfer (both particulate and gaseous), and the relative impacts to health, IAQ, and occupant comfort.…”
Section: Relevance To Indoor Environmental Qualitymentioning
confidence: 99%